Corporate Internet Reporting, Corporate Social Responsibility, and Cost of Equity : Insight from Malaysia - Hui, Wei You; Rayenda Khresna, Brahmana (Canadian Center of Science and Education, 2017)
This paper deals with the moderating role of corporate internet reporting (abbreviated as CIR) on the relationship between corporate social responsibilities (abbreviated as CSR) on the cost of equity (abbreviated as CoE) covering 690 Malaysian public listed companies in 2014. This paper examines the accuracy of agency theory and contingency theory in explicating CoE in Malaysia. Our results show that CSR has a significant effect on the CoE. However, it shows unexpected sign between CoE and CSR. The result shows negative significant on moderating role of CIR between relationship CSR and CoE. This research implies two important contributions. First, the CSR practice may induce the cost of equity as an investor may see it as the extra cost for the firm. Second, to reduce the cost of CSR disclosure, company should report the activities on the internet, as our result show that after CSR interacts with CIR, it reduces the COE.